Case report: A novel missense variant in melanopsin associates with delayed sleep phenotype: Whole genome sequencing study - Smieszek, Sandra P.; Polymeropoulos, Christos M.; Birznieks, Gunther; Polymeropoulos, Mihael H. (Frontiers in Genetics, 2022)
Melanopsin (OPN4) is a blue light-sensitive opsin-type G-protein coupled receptor. It is highly expressed in photosensitive retinal ganglion cells which mediate responses to light including regulation of sleep, circadian photoentrainment and pupillary light response. Mutations in OPN4 were shown to affect responses to light, ultimately affecting the regulation of circadian rhythms and sleep. In this study, we describe a male carrier of OPN4 missense variant diagnosed with Delayed Sleep–Wake Phase Disorder (DSWPD), with a consistent recurrent pattern of delayed sleep onset The rs143641898, [NM_033282.4:c.502C>T p.(Arg168Cys)] variant in the OPN4 gene was shown in a functional study to render OPN4 protein non-functional. The variant is a rare and likely increasing risk for DSWPD via its direct effect on the melanopsin pathway. This study offers useful insights for the differential diagnosis and ultimately treatment of DSWPD risk in which patients carry pathogenic variants in the OPN4 gene.